2019
DOI: 10.3389/fevo.2019.00203
|View full text |Cite
|
Sign up to set email alerts
|

Predator-Prey Interactions and Eavesdropping in Vibrational Communication Networks

Abstract: Due to human perceptional bias in favor of airborne sounds, substrate-borne vibrational signaling has been traditionally regarded as a highly specialized, inherently short-range and, consequently, a private communication channel, free from eavesdropping by sexual competitors and predators. In this review, we synthesize current knowledge pertinent to the view that most animals live in a rich vibratory world, where vibrational information is available to unintended receivers. In recent years, we realized that vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 156 publications
(223 reference statements)
0
42
0
Order By: Relevance
“…An increasing number of studies have demonstrated how this way of communicating is part of a complex, dynamic network of intraspecific and interspecific signaling, in which conspecifics, heterospecifics, rivals, and exploiters are actively involved in information exchanges (Cocroft et al, 2014;Cocroft & Rodríguez, 2005;Hill et al, 2019;McVean & Field, 1996;Stewart & Zeigler, 1984;Virant-Doberlet et al, 2014;Virant-Doberlet et al, 2019). Vibrational communication is not a private, short-range, highly specialized communication channel with limited use, as was previously thought, compared with acoustic communication, and it is not free from eavesdropping (Hill et al, 2019;Virant-Doberlet et al, 2019). Indeed, as illustrated previously, this communication modality is widely used by animals to manage vital, essential behavioral processes relative, for instance, to reproduction, predator-prey interaction, foraging, and parental care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of studies have demonstrated how this way of communicating is part of a complex, dynamic network of intraspecific and interspecific signaling, in which conspecifics, heterospecifics, rivals, and exploiters are actively involved in information exchanges (Cocroft et al, 2014;Cocroft & Rodríguez, 2005;Hill et al, 2019;McVean & Field, 1996;Stewart & Zeigler, 1984;Virant-Doberlet et al, 2014;Virant-Doberlet et al, 2019). Vibrational communication is not a private, short-range, highly specialized communication channel with limited use, as was previously thought, compared with acoustic communication, and it is not free from eavesdropping (Hill et al, 2019;Virant-Doberlet et al, 2019). Indeed, as illustrated previously, this communication modality is widely used by animals to manage vital, essential behavioral processes relative, for instance, to reproduction, predator-prey interaction, foraging, and parental care.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, within this network of signaling, every single individual can act both as the sender or receiver and as the eavesdropper (Greenfield, 2010;Hill et al, 2019;Hill & Wessel, 2016;Sitvarin, Gordon, Uetz, & Rypstra, 2016). Among the other sensory systems (sight, hearing, touch, smell) used to communicate and intercept environmental signals, animals also possess highly sensitive receptors able to detect substrate vibrations (Virant-Doberlet et al, 2019). Table 1 illustrates the mechanoreceptors known in invertebrates (Keil, 1997(Keil, , 2001.…”
Section: Predation Defense Strategies and Eavesdroppingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sound receptors have not been described in O. fagi, so whether it receives acoustic cues as signals transported through the air or as vibratory signals transported through the substrate (Dobai, 2018;Takanashi et al, 2019;Virant-Doberlet et al, 2019) is unknown. Communication through substrate (e.g., host plant) vibrations is widespread in insects ( Cokl & Virant-Doberlet, 2003;Cocroft & Rodriguez, 2005), including beetles, of which some species are known to detect vibrations with chordotonal organs in their femurs (e.g., Takanashi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Insects use vibrations in varied contexts. These include, for example, detection of passive cues (from abiotic or biotic sources), reproduction, territorial displays, recruitment, and other social interactions (Virant-Doberlet and Cokl 2004;Cocroft and Rodriguez 2005;Hill 2008;Cocroft and Hamel 2010;Yack 2016;Virant-Doberlet et al 2019) The majority of these studies are focused on adults (mainly reproductive behaviours), with a limited number of studies in juveniles (eggs, larvae, nymphs and pupae). Yet, emerging studies suggest the use of vibrations by juveniles in diverse contexts; for example, egg hatching (Endo et al 2019), social group coordination and recruitment (Hograefe 1984;Fletcher 2007Fletcher , 2008; also see Chapter 4), parasitic or mutualistic interactions with ants (Devries 1990;Travassos and Pierce 2000), food acquisition (Ishay 1974;Hograefe 1984;McIver and Beech 1986), territoriality and spacing (Yack et al 2001(Yack et al , 2014Fletcher et al 2006;Scott et al 2010;Guedes et al 2012), and predator and parasitoid detection and avoidance (Castellanos and Barbosa 2006;Low 2008;Gish et al 2012;Kojima et al 2012).…”
Section: Vibroacoustics and The Role Of Vibrations In Grouping Behaviourmentioning
confidence: 99%